Optical sectioning in fluorescence microscopy. - Wilson, T (2011)
We review the origins of optical sectioning in fluorescence microscopy in terms of the structure of the illumination used to generate the fluorescence within the specimen. We note that the conventional microscope using essentially uniform illumination does not exhibit optical sectioning whereas the confocal microscope using point (many spatial frequencies) illumination does. We show that the optical sectioning strength of a confocal microscope is not optimal and discuss the advantages of using a single spatial frequency for the structure of the illumination and the detection. In this case the optical sectioning strength is shown to be up to 25% narrower than in the ideal confocal case.